2022
DOI: 10.1080/21655979.2022.2062103
|View full text |Cite
|
Sign up to set email alerts
|

The interferon regulatory factor 6 promotes cisplatin sensitivity in colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignancies and causes of cancer-related mortality worldwide. Cell proliferation and tumor metastasis as well as chemoresistance are correlated with poor survival of CRC. The interferon regulatory factor 6 (IRF6) is functioned as a tumor suppressor gene in several cancers and is associated with risk of CRC. We explored the role of IRF6 in CRC in the present study. The protein expressions of IRF6 in human CRC tissues, normal para-carcinoma tissue and liver meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We also predicted patients’ drug sensitivity to chemotherapy and observed that C2 cluster was more sensitive to these common chemotherapy drugs. Cisplatin and Imatinib (STI571) has also been used for CRC treatment [ [45] , [46] , [47] ]. In vitro study, we found that Sunitinib drug eluting beads and Dasatinib could effectively inhibit the growth of human CRC cells [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted patients’ drug sensitivity to chemotherapy and observed that C2 cluster was more sensitive to these common chemotherapy drugs. Cisplatin and Imatinib (STI571) has also been used for CRC treatment [ [45] , [46] , [47] ]. In vitro study, we found that Sunitinib drug eluting beads and Dasatinib could effectively inhibit the growth of human CRC cells [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified a group of enhancer-associated genes regulated by ΔNp63 and YAP5SA, many of which have previously been shown to be involved in cell migration and adhesion. One example is interferon regulatory factor 6 (IRF6) which was strongly downregulated by YAP5SA and which has been shown to inhibit migration and cell invasion in squamous cell carcinomas and colorectal cancer cells ( 78 , 79 ). Further investigation is required to determine whether suppression of IRF6 contributes to YAP-mediated migration.…”
Section: Discussionmentioning
confidence: 99%
“…IRFs show an imbalance expression and played different roles in the occurrence and development of in many different cancers [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. IRF6 might enhance chemotherapeutic sensitivity of cisplatin in colorectal cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…IRFs show an imbalance expression and played different roles in the occurrence and development of in many different cancers [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. IRF6 might enhance chemotherapeutic sensitivity of cisplatin in colorectal cancer [36]. IRF4 was overexpressed and activated the cancer progression by Notch signaling pathway in human non-small-cell lung cancer [37].…”
Section: Discussionmentioning
confidence: 99%